Evaluating the Contribution of Nocardia spp. and Mycobacterium tuberculosis to Pulmonary Infections among HIV and Non-HIV Patients at the Komfo Anokye Teaching Hospital, Ghana - Samuel Asamoah Sakyi; Kwabena Owusu Danquah; Richard Dadzie Ephraim; Anthony Enimil; Venus Frimpong; Linda Ahenkorah Fondjo; Esther Love Darkoh (Canadian Journal of Infectious Diseases and Medical Microbiology)
Tuberculosis (TB) is a major cause of human mortality particularly in association with the human immunodeficiency virus (HIV). Nocardia spp. has emerged as an opportunistic infection especially in HIV patients. The high prevalence of TB and HIV coupled with the lack of a definitive laboratory diagnosis for Nocardia spp. could lead to misdiagnosed pulmonary TB. This study determined the prevalence of pulmonary infections due to Nocardia spp. and Mycobacterium tuberculosis in sputum of HIV and non-HIV patients with suspected pulmonary tuberculosis at KATH. A total of sixty sputum samples were obtained from HIV and non-HIV patients with suspected pulmonary tuberculosis. Samples were examined by fluorescence based Ziehl–Neelsen staining, culture, and PCR methods. The prevalence of Nocardia spp. and Mycobacterium tuberculosis was 18.3% and 20%, respectively, with the latter having the highest rate among patients aged 21–40 years (P=0.075). The prevalence of Nocardia spp. among HIV patients was 90.9% whilst 16.7% of the patients had HIV/Nocardia spp. coinfection. Detection of Mycobacterium tuberculosis by fluorescence-based Ziehl–Neelsen staining, culture, and PCR yielded 9 (15%), 11 (18.3%), and 12 (20%), respectively. There is a high prevalence of nocardiosis especially in HIV patients. PCR is a better diagnostic method that detects both Nocardia spp. and Mycobacterium tuberculosis and should be incorporated into routine diagnosis for pulmonary infections.